Il principio di minimo e sue applicazioni alle equazioni funzionali - Faedo, S.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2011)
L. Nirenberg: On ellliptic partial differential equations.- S. Agmon: The Lp approach to the Dirichlet problems.- C.B. Morrey, Jr.: Multiple integral problems in the calculus of variations and related topics.- L. Bers: Uniformizzazione e moduli.
L. Nirenberg: On ellliptic partial differential equations -- S. Agmon: The Lp approach to the Dirichlet problems -- C.B. Morrey, Jr.: Multiple integral problems in the calculus of variations and related topics -- L. Bers: Uniformizzazione e moduli.
Keywords: Mathematics; Functional equations; Mathematics; Difference and Functional Equations